Нашла себе блондина! - Вильмонт Екатерина Николаевна (Про жизнь и про любовь, 2016)
Экземпляры: Ф. 5 (20191219) / Инвентарный номер: 46100 / Цена: 128.00 / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: В 46 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4